Modification of [18F]FMISO Radiosynthesis by Using a Non-Cassette-Based Synthesizer for Supporting Hypoxia Diagnosis in Cancer Patients in Thailand - Keeratipiriyakul, Jiratthakorn; Sudprasert, Wanwisa (Trends in Sciences, 2022)
In cancer cells, hypoxia can lead to resistance to both radiation and chemotherapy. The ability to measure cellular hypoxia is an useful tool in therapeutic planning. [18F]Fluoromisonidazole ([18F]FMISO) is a specific tracer used for the detection of hypoxic tissues by positron emission tomography (PET). In this research, the [18F]FMISO radiosynthesis has been modified to reduce costs to support clinical studies of patients with hypoxia by using an automated module instead of the disposable cassette-based synthesizer. The Synthra RNplus module, a remote-controlled synthesizer, was used for nucleophilic substitution of NITTP (1-(2’-nitro-1’-imidazolyl)-2-O-tetrahydropyranyl-3-O-toluenesulfonyl-propanediol) with [18F]fluoride anion. Labeling of the 5 mg of NITTP precursor in anhydrous dimethyl sulfoxide (DMSO) was performed at 100 ℃ for 10 min and hydrolyzed with 1 M hydrochloric acid (HCl) at 100 ℃ for 5 min. Finally, the purified product was obtained by using solid phase extraction (SPE) cartridge instead of high-performance liquid chromatography (HPLC). The total [18F]FMISO yield was approximately 29.11 ± 5.00 % (n = 7), the total synthesis time was less than 35 min, and the radiochemical purity was greater than 95 %. These results are very useful for supporting hypoxia diagnosis in cancer patients in Thailand. HIGHLIGHTS Rapid and simplified [18F]FMISO radiosynthesis are very useful for supporting hypoxia diagnosis in cancer patients in Thailand [18F]FMISO radiosynthesis using Synthra RNplus with SPE purification takes less than 35 min [18F]FMISO yield is approximately 29.11 ± 5.00 % (n = 7, non-decay corrected) and the radiochemical purity is greater than 95 % GRAPHICAL ABSTRACT